Gene and cell therapy for pancreatic cancer - Singh, Hans Martin; Ungerechts, Guy; Tsimberidou, Apostolia M. (Expert opinion on biological therapy, 2015)
INTRODUCTION: The clinical outcomes of patients with pancreatic cancer are poor, and the limited success of classical chemotherapy underscores the need for new, targeted approaches for this disease. The delivery of genetic material to cells allows for a variety of therapeutic concepts. Engineered agents based on synthetic biology are under clinical investigation in various cancers, including pancreatic cancer. AREAS COVERED: This review focuses on Phase I - III clinical trials of gene and cell therapy for pancreatic cancer and on future implications of recent translational research. Trials available in the US National Library of Medicine (www.clinicaltrials.gov) until February 2014 were reviewed and relevant published results of preclinical and clinical studies were retrieved from www.pubmed.gov . EXPERT OPINION: In pancreatic cancer, gene and cell therapies are feasible and may have synergistic antitumor activity with standard treatment and/or immunotherapy. Challenges are related to application safety, manufacturing costs, and a new spectrum of adverse events. Further studies are needed to evaluate available agents in carefully designed protocols and combination regimens. Enabling personalized cancer therapy, insights from molecular diagnostic technologies will guide the development and selection of new gene-based drugs. The evolving preclinical and clinical data on gene-based therapies can lay the foundation for future avenues improving patient care in pancreatic cancer.
Gesehen am 04.08.2017